Urban shinkage in a 'shrinking' Serbia – the approach to a global phenomenon in a local context - Aleksandra Djukić; Branislav Antonić; Tijana M. Vujičić (Geodetski Vestnik, 2017)
The initial purpose of this research was to understand the basic patterns of urban shrinkage in Serbia. Urban shrinkage, a common phenomenon in post-socialist countries, is a novelty, albeit very present in Serbia today. Despite presenting a huge challenge for the future of the country, it has not been studied sufficiently at any level. To understand this situation, the first “task” would certainly be to identify which cities in Serbia can be considered as shrinking in a local context. The research will focus on this issue through the development of four models of shrinking cities in Serbia according to globally based factors of urban shrinkage. The aim of the paper is to clarify the potential of their use and to explore the possible locally-based factors of urban shrinkage.